2013
DOI: 10.1007/s00216-013-7523-8
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution time-of-flight mass spectrometry fingerprinting of metabolites from cecum and distal colon contents of rats fed resistant starch

Abstract: Time-of-flight mass spectrometry along with statistical analysis was utilized to study metabolic profiles among rats fed resistant starch (RS) diets. Fischer 344 rats were fed four starch diets consisting of 55 % (w/w, dbs) starch. A control starch diet consisting of corn starch was compared against three RS diets. The RS diets were high-amylose corn starch (HA7), HA7 chemically modified with octenyl succinic anhydride, and stearic-acidcomplexed HA7 starch. A subgroup received antibiotic treatment to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Please, insert Fig.1 The study of metabolism in samples from the digestive tract [22,23] is an emerging field, aimed at the better understanding of microbiota involvement in certain pathologies. These samples require careful pre-analysis, preliminary cleaning of samples of the intestinal contents and tissue extraction of the liver, we chose to lyophilize the samples before metabolite extraction because of their heterogeneity (macromolecules, undigested material, metabolites) [24].…”
Section: Methods Development and Optimizationmentioning
confidence: 99%
“…Please, insert Fig.1 The study of metabolism in samples from the digestive tract [22,23] is an emerging field, aimed at the better understanding of microbiota involvement in certain pathologies. These samples require careful pre-analysis, preliminary cleaning of samples of the intestinal contents and tissue extraction of the liver, we chose to lyophilize the samples before metabolite extraction because of their heterogeneity (macromolecules, undigested material, metabolites) [24].…”
Section: Methods Development and Optimizationmentioning
confidence: 99%
“…The animals were on the feeding regimens for eight weeks prior to sacrifice. For purposes important to companion studies (58,60,61) that used this same diet trial, each diet group was further split up into two or four treatment subgroups. The control and RS5-HA7 diet groups each contained 29 rats that were split up among four subgroups according to whether or not the rats were given injections of the carcinogen azoxymethane (AOM) and whether or not they were treated with an antibiotic.…”
Section: Rat Diet and Treatmentmentioning
confidence: 99%
“…The ability of FTIR-PAS to detect and measure so many different factors in such a wide variety of biological materials makes it a natural choice for analysis of digesta and fecal material in dietary and disease studies, but our recent work reported here and elsewhere (57,58) appears to be the first such uses. The results reported here have also been discussed in our previous publication (57).…”
mentioning
confidence: 91%
“…The composition of the gut microbiome has a high inter-and intraspecies variability in general which makes it difficult to define a healthy gut microbiome regarding the species inhabiting the gut [1,23]. Bacteria are the major part of microorganisms present in the gut microbiome: they outnumber eukaryotes and archaea by 2-3 orders of magnitude [1].…”
Section: Inter-and Intraspecies Variability Of the Gut Microbiomementioning
confidence: 99%
“…However, to depict a more precise picture of gut microbial changes, and with this of interindividual or sex-specific effects, the following classes of metabolites may be useful to gain new insights and could be additionally measured: short chain fatty acids (SCFAs), choline metabolites, phenolic, benzoyl and phenyl derivates, polyphenols and flavonoids, vitamins, and polyamines [20][21][22][23][24][25][26][27]. Other valuable analytes might be dietary carbohydrates and complex glycoconjugates since they are more and more playing a role in the research of how to maintain or restore a healthy gut microbiome [28].…”
Section: Metabolomics Key Metabolites and (Systemic) Effect Of Antibmentioning
confidence: 99%